ANALISIS KOORDINASI SISTEM PROTEKSI RELAI OVERCURRENT PADA JARINGAN DISTRIBUSI UNIT 3A PLTU PAITON - Andreyanto, Tegar Setyo; Dhofir, Moch.; Hasanah, Rini Nur; Siswandi, Wawan (Jurnal Mahasiswa TEUB, 2024)
This research aims to determine the appropriate OCR settings to handle potential short-circuit currents in the distribution network of Unit 3A at Paiton Power Plant under existing load conditions. This study focuses on the Overcurrent Relay (OCR) protection device. The short-circuit current calculations are performed mathematically using the per-unit method and sequence impedance circuit. The OCR resetting calculations in this study apply the British Standard BS-142 for relay current settings, the IEC 60255-151 standard for inverse relay operating time, and the IEEE 242 standard for relay coordination time delay. In this study, short-circuit current simulation and OCR operation simulation are conducted using the ETAP 12.6 application. The results of this research indicate the OCR relay settings as follows: Extremely Inverse with a Pickup of 0.88 and TMS of 0,425, Very Inverse with a Pickup of 0.4 and TMS of 0.1, Long Time Inverse with a Pickup of 0.75 and TMS of 0.025. Additionally, relay coordination with a time delay of 0.2-0.4 seconds is achieved. Based on the simulations, the OCR operates effectively and in compliance with the standards. Keywords— Overcurrent relay, Short Circuit, ETAP, Relay Setting